Assessing the Workforce Diversity and Inclusion in the Oil and Gas Industry - Beatrice Acouth P. K. (Uganda Christian University, 2025)
The study examined the workforce diversity and inclusion in SUDD petroleum operating company, Juba South Sudan. The company's workforce is highly diverse, with 60% of employees from different ethnic backgrounds, 30% female representation in the workforce and 20% of employees from various religious backgrounds. The study was guided by the objectives to examine the collaboration on inclusion, to examine the commitment on inclusion and to examine the ability on inclusion Sudd Petroleum operating Company, Juba South Sudan. The study adopted a descriptive design, the researcher selected 52 respondents using Krejucie, Robert, Morgan, Daryle table of 1970. The correlation analysis revealed a positive and statistically significant relationship between workforce diversity and inclusion at Sudd Petroleum Operating Company. The Pearson correlation coefficient of r = 0.340 indicates a moderate positive relationship, suggesting that as workforce diversity increases, inclusion within the organization also tends to improve. The significance value of p = 0.014 (p < 0.05) confirms that this relationship is statistically significant and not due to random chance. The regression analysis indicates that collaboration, commitment, and ability jointly have a significant but modest effect on inclusion at Sudd Petroleum Operating Company. The model shows a correlation coefficient of R = 0.400, with an R Square of 0.160, meaning that about 16% of the variation in inclusion is explained by the three predictors. The company should invest in building employee competencies through continuous training, mentorship, and skills development programs. The organization should strengthen teamwork and cross-departmental engagement by creating platforms for shared decision-making, promoting transparent communication, and encouraging joint problem- solving. The study concludes that SPOC employees generally possess the skills and capacities to engage inclusively, but gaps remain in managerial capabilities, training provision, and organizational responsiveness to inclusion challenges.